C9orf72 expansion differentially affects males with spinal onset amyotrophic lateral sclerosis. Issue 4 (23rd September 2016) - Rooney, James; Fogh, Isabella; Westeneng, Henk-Jan; Vajda, Alice; McLaughlin, Russell; Heverin, Mark; Jones, Ashley; van Eijk, Ruben; Calvo, Andrea; Mazzini, Letizia; Shaw, Christopher; Morrison, Karen; et al.
Abstract : Introduction: The C9orf72 repeat expansion has been reported as a negative prognostic factor in amyotrophic lateral sclerosis (ALS). We have examined the prognostic impact of the C9orf72 repeat expansion in European subgroups based on gender and site of onset. Methods: C9orf72 status and demographic/clinical data from 4925 patients with ALS drawn from 3 prospective ALS registers (Ireland, Italy and the Netherlands), and clinical data sets in the UK and Belgium. Flexible parametric survival models were built including known prognostic factors (age, diagnostic delay and site of onset), gender and the presence of an expanded repeat in C9orf72. These were used to explore the effects of C9orf72 on survival by gender and site of onset. Individual patient data (IPD) meta-analysis was used to estimate HRs for results of particular importance. Results: 457 (8.95%) of 4925 ALS cases carried the C9orf72 repeat expansion. A meta-analysis of C9orf72 estimated a survival HR of 1.36 (1.18 to 1.57) for those carrying the expansion. Models evaluating interaction between gender and C9orf72 repeat expansions demonstrated that the reduced survival due to C9orf72 expansion was being driven by spinal onset males (HR 1.56 (95% CI 1.25 to 1.96). Conclusions: This study represents the largest combined analysis of the prognostic characteristics of the C9orf72 expansion. We have shown for the first time that the negative prognostic implication of this variant is driven by males with spinal onset disease, indicating a hitherto unrecognised gender-mediated effect of the variant that requires further exploration.